2018
DOI: 10.1097/md.0000000000012020
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous nerve electrical stimulation for fatigue caused by chemotherapy for cervical cancer

Abstract: This retrospective study investigated the effectiveness of percutaneous nerve electrical stimulation (PNES) for fatigue caused by chemotherapy for cervical cancer survivors.Totally, 83 cases of fatigue caused by chemotherapy for cervical cancer survivors were analyzed. All these cases were assigned to a treatment group (n = 43), and a control group (n = 40). Patients in the treatment group received PNES, while the subjects in the control group were on waiting list. The treatment was applied once daily for a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…To our best knowledge, although lots of clinical trials regarding the effectiveness of ES on AEs caused by chemotherapy in patients with CC were conducted, [20–33] no systematic review specifically focused on the ES for AEs caused by chemotherapy in patients with CC. Therefore, the purpose of this study is to evaluate the effectiveness of ES on different AEs resulted from chemotherapy on CC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our best knowledge, although lots of clinical trials regarding the effectiveness of ES on AEs caused by chemotherapy in patients with CC were conducted, [20–33] no systematic review specifically focused on the ES for AEs caused by chemotherapy in patients with CC. Therefore, the purpose of this study is to evaluate the effectiveness of ES on different AEs resulted from chemotherapy on CC.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, numerous clinical trials have reported that electrical stimulation (ES) can be used to treat AEs caused by chemotherapy effectively and safely. [20–33] However, up to date, no systematic review has systematically investigated the effectiveness and safety of ES for AEs result from chemotherapy in patients with CC. Therefore, in this systematic review, we aim to assess the effectiveness and safety of ES for AEs caused by chemotherapy in patients with CC.…”
Section: Introductionmentioning
confidence: 99%
“…Improper handling of stress response can cause psychological disorders to varying extents. [4,5] Adverse psychological conditions like anxiety, depression and fear can negatively affect psychological and emotional well-being and reduce the quality of survival of patients. [6,7] Therefore, interventions to alleviate negative emotions in patients after cervical cancer surgery are particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…As a kind of stressor, surgical treatment of cervical cancer will, to a large extent, lead to strong stress psychological reactions like anxiety and depression. Improper handling of stress response can cause psychological disorders to varying extents [4,5] . Adverse psychological conditions like anxiety, depression and fear can negatively affect psychological and emotional well-being and reduce the quality of survival of patients [6,7] .…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy is recognized an effective way during the anti-cancer treatment, while it has greatly improved overall survival in variety types of cancers, also brings side effects, such as chemotherapy-induced nausea and vomiting (CINV), [ 3 , 4 ] chemotherapy-induced diarrhea (CID), [ 5 , 6 ] chemotherapy-induced constipation (CIC), [ 5 ] pain, [ 7 ] and fatigue, [ 8 ] which were greatly interfering the treatment course. Among these toxic side events, chemotherapy-induced gastrointestinal reactions, including CINV, CID and CIC, were the most widely influential and severe symptoms.…”
Section: Introductionmentioning
confidence: 99%